A Joint Prosodic Origin of Language and Music - Brown, Steven (Frontiers in Psychology, 2017)
Vocal theories of the origin of language rarely make a case for the precursor functions that underlay the evolution of speech. The vocal expression of emotion is unquestionably the best candidate for such a precursor, although most evolutionary models of both language and speech ignore emotion and prosody altogether. I present here a model for a joint prosodic precursor of language and music in which ritualized group-level vocalizations served as the ancestral state. This precursor combined not only affective and intonational aspects of prosody, but also holistic and combinatorial mechanisms of phrase generation. From this common stage, there was a bifurcation to form language and music as separate, though homologous, specializations. This separation of language and music was accompanied by their (re)unification in songs with words.